VISUALISASI PETA RSS FINGERPRINT DALAM FASE OFFLINE PADA LOCALIZATION DI LANTAI 3 GEDUNG TEKNIK ELEKTRO UGM MENGGUNAKAN WLAN - chairani chairani; Widyawan Widyawan (Jurnal Informatika, 2013)
This paper discusses about the fingerprint mapping of Received Signal Strength (RSS) WLAN, placed in UGM’s Electrical Engineering (TE) building on 3rd Floor Corridor. RSS WLAN measurements performed by using visualization NetSurveyor software and RSS fingerprint map visualization created using RapidMiner software. Dimension area of 3rd floor of UGM’s TE building is 1696.68 m2 and formed in 1893 grids for each grid is 1 m x 1 m. Measurement of RSS WLAN to 5 access points performed in duration of 1 minute 58 seconds, and produce as many as 86980 record. The results of this research is fingerprint visualization map as calibration of RSS WLAN distribution at JTETI building on the 3rd floor which can be used for the development of indoor localization. Keywords : Fingerprint, RSS, WLAN, Localization.